Achieving Water Efficiency in the Public Sector Through Social Norms - Grecksch, Kevin (Frontiers in Environmental Science, 2021)
Water efficiency campaigns in England and Wales currently focus on private domestic customers and private businesses and usually focus on either the implementation of technological devices, financial incentives or educational programs for school children. This brief research report focuses on the public sector (schools, hospital, universities, local government), an underexplored area for investigating the role ofwater savings, and social norms in facilitating water saving. It takes the approach that the public sector provides so far untapped potential for water savings and asks how water saving behavior can be changed. Based on a review of academic, grey literature, documents and a workshop with stakeholders from water companies, regulators and public sector organizations, nine key themes are presented and discussed. The themes, which can also be understood as recommendations, emphasize that water saving behavior is influenced not just by individual decisions, but social and psychological drivers such as social norms, values or group behavior. For example, water saving competitions among different departments, embedding water into the bigger environmental story or the question of who delivers the water saving message may contribute toare of great importance for successfully changing water saving behavior at the workplace1. The public sector is well placed to implement water efficiency programs involving social norms and could act as role model for other sectors.